Progressive structural and covariance connectivity abnormalities in patients with Alzheimer’s disease - Xiao, Yaqiong; Wang, Jiaojian; Huang, Kaiyu; Gao, Lei; Yao, Shun, for the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s disease (AD) is one of most prevalent neurodegenerative diseases worldwide, characterized by cognitive decline and brain structure atrophy. While studies have reported substantial grey matter atrophy related to the progression of AD, it remains unknown about brain regions with progressive grey matter atrophy, structural covariance connectivity of these regions, and associations between the progressive grey matter atrophy and cognitive decline in AD patients. Here, we analyzed neuroimaging data of healthy controls (HC, n = 45) and AD patients (n = 40) at baseline (AD-T1) and one-year follow-up (AD-T2) obtained from the Alzheimer’s Disease Neuroimaging Initiative. The AD-related grey matter atrophy, structural covariance connectivity, and the clinical relevance of grey matter atrophy were examined. The results showed clear patterns of grey matter atrophy in inferior frontal gyrus, prefrontal cortex, lateral temporal gyrus, posterior cingulate cortex, insula, hippocampus, caudate, and thalamus in AD patients. There was significant atrophy in bilateral superior temporal gyrus (STG) and left caudate in AD patients over a one-year period, and grey matter volume changes in right STG and left caudate were significantly correlated with cognitive decline. Additionally, we found reduced structural covariance connectivity between right STG and left caudate in AD patients. Using AD-related grey matter atrophy as features, there was high discrimination accuracy of AD patients from HC, and AD patients at different time points. This study confirms the progressive grey matter atrophy in AD patients and highlights the important involvement of STG and left caudate in cognitive decline related to the pathological progression of AD.